Subsampling technique to enhance the decoded output of JTC encrypting system (2011)
ABSTRACT: Optical systems have physical restrictions that impose limits in the finest spatial feature that can be processed. In this work we combine a subsampling procedure with a multiplexing technique to overtake the limit on the information that is processed in a JTC encryption system. In the process the object is divided in subsamples and each subsample is encrypted separately. Then the encrypted subsamples are multiplexed. The encryption of the subsamples is performed in a real optical JTC encrypting system. The multiplexing and the decryption process are carried out by means of a virtual optical system. Experimental results are presented to show the validity of the proposal.